(untitled) (Лучшие интеллектуальные исследования, 2024)
More than 12 million tons of chickpea were grown in the world in the last year’s season, and India, Australia, Myanmar, Pakistan, Turkey, Ethiopia, Russia, and Iran are the countries that produce the most chickpeas. Currently, the possibility of meeting the demand for chickpea grain from the crop grown in our republic is very low. In the study, 20 winter chickpea genotypes were evaluated and selected under irrigated field conditions. Winter chickpea genotypes were determined by parameters such as growth period, plant height, location of lower pods relative to the soil surface, yield indicators, weight of 1000 grains, NDVI indicator, chlorophyll content, and protein content.